State and Governance in Indonesia: Research Trends, Intersects, and Gaps (2020–2025) - TULIS, RIAMONA SADELMAN; Anyualatha Haridison; Chrismantya Dwi Satriya Nugraha (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Palangka Raya, 2026)
This article conducts a rapid scoping review of scientific literature from the period 2020-2025 to map the dynamics of the relationship between the role of the state and the role of governance in the Indonesian context. This study aims to identify thematic trends, the role of the state, dominant governance models, and points of friction between the two. Analysis of 305 articles reveals a paradigm shift from a hierarchical and centralized state model towards collaborative, adaptive, and networked governance. The state plays a multidimensional role, not only as a regulator and service provider, but also as a facilitator, catalyst, and digital innovator. Meanwhile, collaborative governance, digital governance, and sustainable governance emerged as the most dominant modes of governance. The main points of convergence and tension lie in the effort to balance state sovereignty with inclusive network logic, as well as the challenge of accountability in multi-actor collaboration models. The article concludes by presenting a concise map, a comparative matrix, and a future research agenda to address critical knowledge gaps, such as digital sovereignty governance, green bureaucratic capacity, and intersectional approaches to governance.